Prevalence of comorbid substance use, anxiety and mood disorders in epidemiological surveys, 1990–2014: A systematic review and meta-analysis - Lai, Harry Man Xiong; Cleary, Michelle; Sitharthan, Thiagarajan; Hunt, Glenn E. (Drug and alcohol dependence, 2015)
•A systematic review was conducted to assess comorbidity between substance use, mood and anxiety disorders.•Meta-analysis showed the strongest associations were for drug use and major depression (OR 3.80).•People with an alcohol use disorder were 2.1 times of greater risk having an anxiety disorder than non-users.•Comorbidity was higher for people with drug or alcohol dependence than those with abuse.•Comorbid prevalence rates were similar between current (1 year) and lifetime drug or alcohol users. Comorbidity is highly prevalent between substance use disorders (SUDs), mood and anxiety disorders. We conducted a systematic review and meta-analysis to determine the strength of association between SUDs, mood and anxiety disorders in population-based epidemiological surveys. A comprehensive literature search of Medline, EMBASE, CINAHL, PsychINFO, Web of Science, and Scopus was conducted from 1990 to 2014. Sources were chosen on the basis that they contained original research in non-clinical populations conducted in randomly selected adults living within defined boundaries. Prevalence of comorbid SUDs, mood and anxiety disorders and odds ratios (ORs) were extracted. There were 115 articles identified by electronic searches that were reviewed in full text which yielded 22 unique epidemiological surveys to extract lifetime and 12-month prevalence data for psychiatric illness in respondents with an SUD. Meta-analysis indicated the strongest associations were between illicit drug use disorder and major depression (pooled OR 3.80, 95% CI 3.02–4.78), followed by illicit drug use and any anxiety disorder (OR 2.91, 95% CI 2.58–3.28), alcohol use disorders and major depression (OR 2.42, 95% CI 2.22–2.64) and alcohol use disorders and any anxiety disorder (OR 2.11, 95% CI 2.03–2.19). ORs for dependence were higher than those for abuse irrespective to diagnoses based on lifetime or 12-month prevalence. This review confirms the strong association between SUDs, mood and anxiety disorders. The issue has now been recognised worldwide as a factor that affects the profile, course, patterns, severity and outcomes of these disorders.